2021
DOI: 10.1021/acs.joc.0c02778
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylation of Self-Immolative Thiocarbamates Provides Insights into the Mechanism of Carbonyl Sulfide Release

Abstract: Hydrogen sulfide (H 2 S) is an important biomolecule, and selfimmolative thiocarbamates have shown great promise as triggerable H 2 S donors with suitable analogous control compounds; however, thiocarbamates with electron-deficient payloads are less efficient H 2 S donors. We report here the synthesis and study of a series of N-methylated esterase-triggered thiocarbamates that block the postulated unproductive deprotonation-based pathway for these compounds. The relative reaction profiles for H 2 S release acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Specifically, donors with low p K a values R ‐ NH 2 have a relatively faster H 2 S‐releasing rate than the donors with high p K a values R ‐ NH 2 . From the electronic effects point of view, the results obtained from this study might also be explained by the most recent work of Pluth' group 111 . The tunable H 2 S‐releasing properties and a well‐defined mechanism of carbamothioate‐based COS/H 2 S donors make donor 65 has superior advantages over other types of COS/H 2 S donors.…”
Section: H2s Donors and H2s‐releasing Hybrid Moleculessupporting
confidence: 71%
See 4 more Smart Citations
“…Specifically, donors with low p K a values R ‐ NH 2 have a relatively faster H 2 S‐releasing rate than the donors with high p K a values R ‐ NH 2 . From the electronic effects point of view, the results obtained from this study might also be explained by the most recent work of Pluth' group 111 . The tunable H 2 S‐releasing properties and a well‐defined mechanism of carbamothioate‐based COS/H 2 S donors make donor 65 has superior advantages over other types of COS/H 2 S donors.…”
Section: H2s Donors and H2s‐releasing Hybrid Moleculessupporting
confidence: 71%
“…The kinetic experimental results showed that the thiocarbamate‐based donor 59 with R = EDGs were fast and potent H 2 S donors, whereas with R = EWGs were slow and poor H 2 S donors. The mechanisms underlying this experimental fact might be explained by the most recent work of Pluth's group, 111 although the authors of this study proposed another isothiocyanate‐generating mechanism. Donor 60 was rather unstable in solution (probably owing to the existence of a thioester group) and toward ROS (demonstrated by using a model compound without arylboronate trigger; the statement about stability toward ROS in the following part is conducted using model compounds without arylboronate trigger), and thus they released less H 2 S in a slow rate.…”
Section: H2s Donors and H2s‐releasing Hybrid Moleculesmentioning
confidence: 84%
See 3 more Smart Citations